Perbandingan Kemampuan Inkuiri Mahasiswa Pendidikan Guru Sekolah Dasar dalam Perkuliahan Sains - Chandra Ertikanto (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2017)
The aim of this research is to describe the inquiry ability (knowledge and skill) and the response from students of Elementary School Teachers Education (PGSD) Lampung University towards Elementary School (SD) Science Education Lecture. The research is done with modeling the inquiry learning model, where PGSD students play as SD learners, and the researcher as SD teacher model. Sampling technique used is Quota Sampling, which means random sampling until fulfilled the number wanted. This research is done on 72 students, and start from March to June 2016. Inquiry ability of variable achieved from multiple choice test, and the student' response achieved through questionaire. The data analysis is using computerized statistic. The research result that: inquiry ability of PGSD students after following SD Science Lecture through modeling inquiry learning model, significantly higher than convensional inquiry learning model. On experimental group seems anthusias, and gives positive response, PGSD students hope the SD labeling lectures can be done by modeling inquiry learning model.